Dynamics of pulses trade in India - Chandra, Raj; Joshi, Pramod Kumar; Negi, Akanksha; Roy, Devesh (International Food Policy Research Institute, 2017)
During the past decade, because of the persistent deficit in India’s pulse sector, the sharp rise in pulse prices has coincided with significant changes in the nature and extent of the pulse trade. Surprisingly, no systematic study has been done on the evolution of this trade, despite the fact that the role of trade in the price formation of pulses is becoming increasingly important. This chapter attempts to fill this research gap. Since exports of pulses from India are comparatively small, we focus on imports.